Universality in gelation of epoxy acrylate with various photoinitiators: a photo differential scanning calorimetric study - Dogruyol, Z.; Karasu, F.; Balta, D. K.; Arsu, N.; Pekcan, Oe. (TAYLOR & FRANCIS LTD, 2008)
Photo-differential scanning calorimetric (Photo-DSC) technique was used to study the gelation of P-3038 (epoxy acrylate (EA) 75% and tripropyleneglycoldiacrylate (TPGDA) 25%) in the presence of various thioxanthone-based initiators, namely, thioxanthone (TX), 5-thia-naphtacene-12-one (TX-NP), 2-(carboxymethoxy) thioxanthone (TX-OCH2COOH), 2-thioxanthone-thioacetic acid (TX-SCH2COOH), and 2-mercaptothioxanthone (TX-SH). Photopolymerization reactions were performed under identical conditions of temperature, initiator concentration, and UV light intensity. Photo-DSC technique allowed us to monitor the gelation, without disturbing the system mechanically, and to test the universality of the gelation as a function of some kinetic parameters like initiator concentration. During gelation, it was observed that all conversion curves present a good sigmoidal behavior by predicting to employ percolation model. Observations around the glass transition point, t(g) shows that the gel fraction exponents beta obeyed the percolation picture. On the other hand, t(g) was found to be much higher for the crosslinked networks obtained with TX-OCH2COOH and TX-SCH2COOH initiators than those with the other initiators.
Keywords: critical exponent; photoinitiator; epoxy acrylate; photo-DSC; glass transition point; FREE-RADICAL POLYMERIZATION; CROSS-LINKING COPOLYMERIZATION; MOLECULAR-SIZE DISTRIBUTION; METHYL-METHACRYLATE; GLASS-TRANSITION; FLUORESCENCE TECHNIQUE; BULK-POLYMERIZATION; PERCOLATION; POLYMERS; VISCOELASTICITY; Crystallography; Physics